1976
DOI: 10.1016/s0022-5347(17)59324-6
|View full text |Cite
|
Sign up to set email alerts
|

The Ureteral Stump after Nephroureterectomy

Abstract: Herein we review 70 cases of transitional cell carcinoma of the upper urinary tract. When complete nephroureterectomy was not performed transitional cell carcinoma developed in 30 per cent of the remaining ureteral stumps. Single incision nephroureterectomy did not include the intramural ureter in 50 per cent of the cases in which it was performed. When nephroureterectomy is selected as treatment for carcinoma of the renal pelvis or ureter a cuff of bladder, which includes the ureteral orifice, should be remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…In 60% of cases, nephrectomy without ureterectomy was performed and average survival was 6 months (17,18). Renal UC has a propensity to recur in the ipsilateral ureter at a rate of 30 to 40% and mandates radical nephroureterectomy (19,20). In one of our patients, with the presumed diagnosis of RCC, the ureter was left in situ.…”
Section: Commentsmentioning
confidence: 85%
“…In 60% of cases, nephrectomy without ureterectomy was performed and average survival was 6 months (17,18). Renal UC has a propensity to recur in the ipsilateral ureter at a rate of 30 to 40% and mandates radical nephroureterectomy (19,20). In one of our patients, with the presumed diagnosis of RCC, the ureter was left in situ.…”
Section: Commentsmentioning
confidence: 85%
“…One advantage of antegrade pyelography is that it is relatively easy to obtain a complete ureterogram of the affected side in combina tion with retrograde pyelography. Many authors have reported that the recurrence rate in the bladder was between 20 and 40% [1,8], However, they did not mention the relationship between the histo logic form of the primary cancers and the rate of recur rence. In our study, 16 patients (30.2%) out of the two groups had a recurrence in the bladder and were treated with transurethral resection, except for 1 patient Clinical Outcome of Ureteral Cancer Urol Int 1997;58: [13][14][15][16][17][18][19] (group B) who underwent a total cystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of recurrent carcinoma of the ureteral stump after imcomplete nephroureterectomy for transi tional cell carcinoma of the upper urinary tract ranges from 20 to 58% [10][11][12][13], For this reason complete neph roureterectomy with removal of the intramural segment is considered the treatment of choice for primary tumors of the upper urinary tract.…”
Section: Discussionmentioning
confidence: 99%